Analisa Pengadaan dan Pengaruhnya Logistik Obat di RS Xyz Pamulang Berdasarkan Metode Abc Ven - Silas Suryawijaya (Syntax Literate, 2023)
This research analyzes the influence of factors that influence the efficiency of drug logistics at Permata XYZ Hospital. The research results show that drug procurement methods, procurement process efficiency, ABC VEN method, and staff training and expertise have a significant influence on drug logistics efficiency. Better procurement methods can improve the availability and use of medicines, procurement process efficiency contributes to efficient medicine logistics management, and the ABC VEN method helps reduce waste of resources and procurement costs. In addition, the training and expertise of medical and non-medical staff play an important role in managing drug supply, distribution and more efficient use of resources. Recommendations include increased transparency in the procurement process, automation of the procurement process, use of integrated information systems, better collaboration with drug suppliers, as well as investment in staff training in drug inventory management, use of information systems, and best procurement practices. These findings provide valuable guidance for Permata Pamulang Hospital in their efforts to improve operational efficiency and patient service.